(untitled) (Boston, 1998)
A concise introduction to computer concepts, this reference book covers traditional core topics, each introduced and exemplified over two pages, illustrated by photographs and line art. It is written to integrate with the multimedia CD-ROM "PACE", which is packaged with the book.
Keywords: Information technology,Công nghệ thông tin